Efektivitas PJBL-Mind Mapping Terhadap Keterampilan Menulis Teks Tanggapan Siswa SMP - Rahma, Affifatul; Ulya, Ridha Hasnul; Nursaid, Nursaid; Anggraini, Dewi (Universitas Pakuan, 2026)
THE EFFECTIVENESS OF PJBL-MIND MAPPING ON JUNIOR HIGH SCHOOL STUDENTS' RESPONSE WRITING SKILLS The low writing skills of response texts of grade VII students of SMP Negeri 25 Padang are the background of this research. The main problems include students' difficulties in developing ideas systematically and low mastery of spelling (EYD). This study aims to test the effectiveness of Project Based Learning (PjBL)-mind mapping on writing skills of response texts based on short film objects. The research method used was a pre-experiment with a One-Group Pretest-Posttest design. The research sample consisted of 32 grade VII.4 students selected through a purposive sampling technique. The research instrument was a writing performance test assessed using a standardized rubric. The results of data analysis showed a significant increase in the average score from 48.437 (Almost Enough) in the pretest stage to 80.859 (Good) in the posttest stage. Hypothesis testing through Paired Sample T-Test produced a Sig. value. 0.000 < 0.05, supported by an Effect Size (Cohen's d) value of -2.768 (very strong category) and an N-Gain Score of 62.87% (moderate category). These findings prove that the synergy between PjBL and visual idea mapping through short films is effective in organizing students' critical ideas systematically.